إدمان الإنترنت وعلاقته بالعوامل الخمس الكبرى للشخصية لدى عينة من طلاب الجامعة بدولة الكويت - المويزري، ناصر شباب; المذكوري، سميرة حسن; الحربي، سعود نامي سعود (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2016)
الأهداف: بالتعرف على العلاقة بين إدمان الإنترنيت والعوامل الخمس الكبرى للشخصية. العينة: تكونت عينة الدراسة من 121 مفحوصا من الذكور والإناث والتي تتراوح أعمارهم ما بين (17-32) سنه من طلاب المرحلة الجامعية بدولة الكويت. الأدوات: تكونت من ميقاس إدمان الإنترنت من إعداد بشرى إسماعيل ومقياس العوامل الخمس الكبرى من إعداد John, Donahue, and kentle تعريب وتقنين بشرى إسماعيل. النتائج: أشارت إلى وجود علاقة طردية عند مستوى دلالة 0.01 بين إدمان الإنترنت والعصابية، ووجود علاقة عكسية عند مستوى 0.01 بين إدمان الإنترنت والانبساطية ويقظة الضمير، كما وجدت علاقة ارتباطيه سالبه عند مستوى 0.05 بين إدمان الإنترنت والمقبولية والتفتح، كما اتضح عدم وجود فروق ذات دلاله إحصائية بين الذكور والإناث على متغير إدمان الإنترنت، كما اتضح وجود فروق دالة إحصائيا بين الذكور والإناث. على متغير السيطرة أو البروز عند مستوى دلالة 0.01 لصالح الإناث، كما وجدت فروق دالة على متغير الصراع عند مستوى 0.05 لصالح الذكور، كما لم يتضح وجود فروق دالة بين الذكور والإناث على المتغيرات تغيير المزاج، والتحمل، والأعراض الإنساحبية، والصراع والانتكاس، وعدم وجود فروق ذات دلالة إحصائية بين الفئات العمرية الثلاث على متغيرات مقياس إدمان الإنترنت، كذلك يتضح وجود فروق دالة إحصائيا عند مستوى 0.01 بين الفئات العمرية الثلاث على بعد تغيير للمزاج بين الفئة العمرية (17-22) والفئة (28-32) لصالح الفئة العمرية (17-22).
Objective: This study aims at examining the Relationship between Internet Addiction and the major five factors of personality Samples: Study consists of 121 males and Females of university students stage in Kuwait. Instruments: Internet addiction measure prepared By Bushra Ismail and a list of major Five factors of personality prepared By John, Donahue, and Kentle Which are localized and coded by Bashra Ismail. Results: Results of this study indicate that there is direct relationship at level 0.01 between Internet addiction and neuroticism and inverse relationship at level 0.01 between Internet addiction, and extensibility and Conscientiousness. There is also a negative relationship at level 0.01 between Internet addiction, and acceptability and open- mindedness. Moreover, there are no statistically significant differences between males and females regarding the variant of Internet addiction. On the contrary, there are statically significant differences between males and females with respect to the variant of control or prominence at level 0.01 for the favor of females while there are statically significant differences between males and females regarding the variant of conflict at level 0.01 for the favor of males. It is not clear that there are any significant differences between males and females in connection with the variants of mood, tolerance, withdrawal symptoms, conflict and inversion and there are no statistically significant differences among the three age groups on the variants of Internet addiction measure. It is found that there are statistically significant differences at level 0.01 among the three age groups in relation to the variant of mood change, particularly between (17- 22) and (28- 32) for (17- 22) groups.
Keywords: الشخصية -- عوامل الشخصية -- إدمان الإنترنت -- طلبة الجامعة -- الكويت